Records Committee review for rare bird sighting of Lesser Black-backed Gull at Elk Rock State Park, 1986 - Petersen, Peter C.et al (1986)
Records Committee review for a Lesser Black-backed Gull at Elk Rock State Park in Marion County, IA on December 3, 1986. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed